Training on the Implementation of Project Based Learning (PBL) Based on Literacy at the Elementery School Level - Saidatun Nafisah; Iwan Budiarso (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
The Kurikulum Merdeka is a curriculum concept launched by the Indonesian Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) in 2021. Using this curriculum, schools can determine the right types and methods of learning for their students, as well as develop curricula that are more relevant to local and global needs. Overall, the PBL (Project Based Learning) method is very much in line with the concept of this curriculum because it provides the freedom, flexibility, and relevance needed in more effective and meaningful learning for students. PBL can also help teachers develop a more dynamic and flexible curriculum, as well as provide opportunities for students to be actively involved in the learning process. Improving literacy and numeracy is one of the main focuses in this curriculum. Literacy and numeracy are considered basic skills that every student must master, as these skills are important in living daily life, learning in the future, as well as participating in an increasingly complex society. It is because  this curriculum is relatively new and not all schools can implement PBL, teachers need models of how to practice it. Thus, the researchers provide training on the application of PBL to elementary school teachers in cluster 04 Ciputat. In accordance with the researcher's field of expertise, the training on the application of PBL takes the realm of literacy.